Feeding frequency efficacy on biogas yield of oily substrate anaerobic digestion in continuous stir tank reactor - Rasit, Nazaitulshila; Wan Ab Karim Ghani, Wan Azlina; Che Harun, Mohammad Hakim; Hamzah, Sofiah (IWA Publishing, 2024)
Anaerobic treatment of oily substrate, known as grease trap waste (GTW), was investigated for its practicability via continuous stirred tank reactor (CSTR) at different operating conditions and selected recovery strategies of feeding frequency efficacy. This study determine the performance of feeding frequency efficacy, namely feeding every 24 hours (R24H) and feeding every 12 hours (R12H). Under organic loading rate (OLR) of 2.2 gCOD/L.day, R12H exhibited methane composition of 57%, methane production rate of 0.27 LCH4/L.day, and methane yield of 0.14 LCH4/gCODremoved. At the same OLR, R24H recorded methane composition of 60%, methane production rate of 0.29 LCH4/L.day and similar methane yield as R12H. Findings indicated that R24H showed performance comparable to that of R12H. Given minor variation observed in performance, it is recommended that plant operators may consider scheduling two feedings per day for low loading conditions and switch to one feeding per day for higher loading conditions. This strategy is designed to balance the system and prevent shock loads, which could lead to plant shutdowns. This mechanism will induce their conversion to volatile fatty acids (VFAs); thus, reducing the risk of acid accumulation and pH drops, which could inhibit methanogens to produce methane, especially for oily substrate.